1990
DOI: 10.1007/bf01740777
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy reduces noradrenaline but not neuropeptide levels in the uterine artery of the guinea-pig

Abstract: Using histochemical, immunohistochemical and biochemical techniques, noradrenaline-, neuropeptide Y-, vasoactive intestinal polypeptide-, substance P- and calcitonin gene-related peptide-containing nerve fibres were studied in the uterine artery of virgin, progesterone-treated and pregnant guinea-pigs. Morphological changes following hormone treatment or in pregnancy were also evaluated in a quantitative study on semithin sections of the uterine artery. In late pregnancy, the number of noradrenaline-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…A network of catecholamine-containing nerves was clearly visible in stretched preparations. The density was greater in tissues obtained from virgin animals, similar to the observations of Mione et al [21]. Cross sections were then treated with glyoxylic acid, and fluorescent varicosities were found to be in greater density close to the outer edge of the smooth muscle in virgin preparations, whereas they appeared to be dispersed throughout the adventitia and further from the smooth muscle in late pregnancy (fig.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…A network of catecholamine-containing nerves was clearly visible in stretched preparations. The density was greater in tissues obtained from virgin animals, similar to the observations of Mione et al [21]. Cross sections were then treated with glyoxylic acid, and fluorescent varicosities were found to be in greater density close to the outer edge of the smooth muscle in virgin preparations, whereas they appeared to be dispersed throughout the adventitia and further from the smooth muscle in late pregnancy (fig.…”
Section: Resultssupporting
confidence: 74%
“…Fluorescence histochemistry of stretched preparations revealed a decrease in the density of the catecholamine innervation during pregnancy and this was confirmed using HPLC to measure the content and concentration of noradrenaline in the uterine artery, similar to the observations of others [21]. Despite this, the amplitude of the slow depolarization that resulted from the activation of α-adrenoceptors appeared similar in tissues from virgin and late pregnant animals.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…An important target organ for SP is the uterus. lrnmunocytochemical studies have shown that numerous SP-positive neurons innervate the myometrium and uterine arteries [3][4][5]. SP, in combination with other neuropeptides, plays an essential role in the regulation of myometrial activity and, consequently, in the maintenance of pregnancy and parturition.…”
mentioning
confidence: 99%